Factor the four-term polynomial.
pq - 3r + pr - 3q

Question

Asked 9/25/2014 11:52:56 AM

Updated 9/25/2014 2:32:26 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [9/25/2014 2:30:42 PM], Confirmed by andrewpallarca [9/25/2014 2:30:43 PM]

s

japs2310qa|Points 1989|

= 6y - 14 - 10y + 5y^2

= 5y^2 - 4y - 14

= -x^2(y^2 - x^2) + 9(y^2 - x^2)

= (y^2 - x^2)(-x^2 + 9)

= (y + x)(y - x)(3 + x)(3 - x)

= (x + 3)(x - 3)(x + y)(x - y)

sharpies|Points 8877|

= x^2(x + 6) - 4(x + 6)

= (x + 6)(x^2 - 4)

= (x + 6)(x + 2)(x - 2)

= a(2y^2 + 5y - 3)

= a(y + 3)(2y - 1)

= -k(2 + k^2 + 3k)

= -k(k^2 + 3k + 2)

= -k(k +1)(k +2)

yeswey|Points 19211|

= 5(x^2 + 2x - 8)

= 5(x + 4)(x - 2)

Question

Asked 9/25/2014 11:52:56 AM

Updated 9/25/2014 2:32:26 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [9/25/2014 2:30:42 PM], Confirmed by andrewpallarca [9/25/2014 2:30:43 PM]

Rating

8

(5x^2 + 2x - 3)(x - 1)

= 5x^3 + 2x^2 - 5x^2 - 3x - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

= 5x^3 + 2x^2 - 5x^2 - 3x - 2x + 3

= 5x^3 - 3x^2 - 5x + 3

Added 9/25/2014 2:32:26 PM

This answer has been confirmed as correct and helpful.

Simplify (2n + 5) - (3n + 7) + (4n - 9). **Weegy:** (2n + 5) - (3n + 7) + (4n - 9) = 2n + 5 - 3n - 7 + 4n - 9 = (2n - 3n + 4n) + (5 - 7 - 9) = 3n + - 11 **User:** Subtract -2k^3 + k^2 - 9 from 5k^3 - 3k + 7. **Weegy:** 5k^3 - 3k + 7 - (-2k^3 + k^2 - 9) = 7k^3 - k^2 - 3k + 16 **User:** Find the sum of 5m + 3n + p, -5p + 3n, and 2n - m. **Weegy:** (5m + 3n + p) + (-5p + 3n) + (2n - m) = 4m + 8n - 4p
**User:** Find the sum of 2x^2 + 3x - 4, 8 - 3x, and -5x 2 + 2. **Weegy:** 2x^2 + 3x - 4 + 8 - 3x + (-5x^2 + 2) = -4 + 8 + 2 + 3x - 3x + 2x^2 - 5x^2; = -3x^2 + 6 **User:** Using the polynomials Q = 3x 2 + 5x - 2, R = 2 - x 2, and S = 2x + 5, perform the indicated operation.
Q - [R + S] **Weegy:** Q = 3x^2 + 5x - 2, R = 2 - x^2, and S = 2x + 5 Q - [R + S] = (3x^2 + 5x - 2) - [(2 - x^2) + (2x + 5)] = (3x^2 + 5x - 2) - (2 - x^2 + 2x + 5) = (3x^2 + 5x - 2) - (7 - x^2 + 2x) = 3x^2 + 5x - 2 - 7 + x^2 - 2x = 4x^2 + 3x - 9 **User:** Simplify -3p 3 + 5p + (-2p 2) + (-4) - 12p + 5 - (-8p 3). Select the answer in descending powers of p. **Weegy:** -3p^3 + 5p + (-2p^2) + (-4) - 12p + 5 - (-8p^3) = -3p^3 + 5p - 2p^2 - 4 - 12p + 5 + 8p^3 = (-3p^3 + 8p^3) - 2p^2 + (5p - 12p) + (-4 + 5) = 5p^3 - 2p^2 - 7p + 1 **User:** Simplify a - {b - [c - (d - e) - f] - g}. **Weegy:** a - {b - [c - (d - e) - f] - g} = a - [b - (c - d + e - f) - g] = a - (b - c + d - e + f - g) = a - b + c - d + e - f + g (More)

Question

Updated 9/19/2014 12:46:28 PM

0 Answers/Comments

Factor 6x^2 - 17x + 5 **Weegy:** 6x^2 - 17x + 5 = (3x - 1)(2x - 5) **User:** Find the greatest common factor of 15x^2y^3 and -18x^3yz **Weegy:** The greatest common factor of 15x^2y^3 and -18x^3yz is 3x^2y. **User:** How many terms are in the polynomial abcd + e - fg + h^2? **Weegy:**
The polynomial abcd + e - fg + h^2 has FOUR terms.
**User:** Factor 3x^2 - 15x - 42. **Weegy:**
3x^2 - 15x - 42 = 3(x + 2)(x - 7)
**User:** Simplify m - {n + [p - (m + n - p)]}. **Weegy:** m - {n - [p + (m + n - p)]} = m - [n - (p + m + n - p)] = m - [n - (m + n)] = m - (n - m - n) = m - (-m) = m + m = 2m **User:** Find the quotient.
(6x^2 - x - 40) ÷ (5 + 2x) **Weegy:**
(6x^2 - x - 40) ÷ (5 + 2x) = 3x - 8
**User:** Divide x^4 + 7 by x - 3. **Weegy:** (x^4 + 7) ÷ (x - 3) = x^3 + 3x^2 + 9x + 27 R. 88
to check:
(x^3 + 3x^2 + 9x + 27)(x - 3)
= x^4 - 81 + 88
= x^4 - 7 **User:** Choose the product.
a^3b^2 · 4ab^3 (More)

Question

Not Answered

Updated 9/25/2014 2:38:56 PM

1 Answer/Comment

a^3b^2 · 4ab^3 = 4a^4b^5

Added 9/25/2014 2:38:56 PM

This answer has been confirmed as correct and helpful.

32,548,543

questions answered

There are no comments.